Development of a Fuzzy Controller Applied to the Velocity of a DC Motor - Almeida, João Paulo Lima Silva de; Junior, Vlademir Freire; Cintra, Lillyane Rodrigues; Mendonça, Márcio; Souza, Lucas Botoni de; Montezuma, Márcio Aurélio Furtado (International Journal of Advanced Engineering Research and Science, 2019)
Control system designs are becoming increasingly complex due to the operational requirements of current processes. An alternative way to this fact is the application of intelligent systems. This work presents a design of a fuzzy controller tuned by genetic algorithm and applied to the velocity control of a DC motor. For comparative performance purposes, it is designed and applied a conventional PI controller. In general, the fuzzy controller presented a better result compared with the conventional implementation. Results from computer simulations are presented.